2015
DOI: 10.1016/j.jacr.2015.09.010
|View full text |Cite
|
Sign up to set email alerts
|

Use of Health Information Exchange and Repeat Imaging Costs

Abstract: Purpose The aim of this study was to quantify the association between health information exchange (HIE) use and cost savings attributable to repeat imaging. Methods Imaging procedures associated with HIE were compared with concurrent controls on the basis of propensity score matching over the period from 2009 to 2010 in a longitudinal cohort study. The study sample (n = 12,620) included patients ages 18 years and older enrolled in the two largest commercial health plans in a 13-county region of western New Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…Early estimates of the savings generated by MSeHA pointed towards large financial benefits and a later study indicated lower, but substantial, benefits from it . Several studies have demonstrated that community HIEs can reduce the rate of imaging . Community HIE participation in Wisconsin that linked 5 competitive systems was shown to save $29 per visit .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Early estimates of the savings generated by MSeHA pointed towards large financial benefits and a later study indicated lower, but substantial, benefits from it . Several studies have demonstrated that community HIEs can reduce the rate of imaging . Community HIE participation in Wisconsin that linked 5 competitive systems was shown to save $29 per visit .…”
Section: Resultsmentioning
confidence: 99%
“…51 Several studies have demonstrated that community HIEs can reduce the rate of imaging. 42,43,52 Community HIE participation in Wisconsin that linked 5 competitive systems was shown to save $29 per visit. 53 A Colorado-based community HIE demonstrated that community HIE adoption was associated with reduced lab testing, but the benefits were smaller than anticipated, and another examination of lab testing showed no effect.…”
Section: Impactmentioning
confidence: 99%
“…Use of health information exchange (HIE) is reported to generate ∼$32,460 in estimated annual savings through avoided repeat imaging among 12,620 propensity score matched patients. Although 85% of the avoided studies were basic imaging (X‐rays, ultrasound, and mammography) and 13% were advanced imaging, CT or MR accounted for half of the estimated savings . Interoperability of Health IT plays a critical role to reduce repeating imaging studies.…”
Section: The Basic Strategy Of Value Demonstrationmentioning
confidence: 99%
“…Studies on HIE outcomes have reported modest to moderate reductions in duplicate laboratory and radiology testing [4][5][6], better identification of medication discrepancies and improved medication reconciliation [7]. HIE use has also decreased hospital readmissions and associated costs [8].…”
Section: Introductionmentioning
confidence: 99%